The politics of street-level bureaucracy in Thailand - Krannich, Ronald L. (Philippine Journal of Public Administration, 1978)
A potentially important theoretical and empirical field of comparative inquiry for Southeast Asian specialists is local bureaucratic politics including such factors as local political and governmental behavior, the theoretical developments concerning street-level bureaucracy, and the relationship between the urban policy making process and urban politics. Based on data gathered in Thailand, the general characteristics of local bureaucratic politics are identified and related to a policy perspective that may have general utility for similar studies in other Southeast Asian countries.